The Proliferation and Stemness of Peripheral Blood-Derived Mesenchymal Stromal Cells Were Enhanced by Hypoxia - Wang, Pengzhen; Zhu, Pingping; Yu, Chaosheng; Wu, Jian (Frontiers in Endocrinology, 2022)
This study aimed to address the dilemma of low peripheral blood-derived mesenchymal stromalcell (PBMSC) activity and reduced phenotype in bone or cartilage tissue engineering. Rat PBMSCs (rPBMSCs) were obtained by density gradient centrifugation, and stromal cell characteristics were confirmed by flow cytometry (FCM) and multi-differentiation potential induction experiments. Cell growth curve, viability experiments, and clone formation experiments were performed by[3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] (MTS) and cell counting, and the cell cycle was confirmed by cell FCM. The proliferation signal pathway and stemness-related proteins were detected by molecular methods including Western blot and real-time polymerase chain reaction. CD73, CD90 and CD105 were highly expressed, and CD14, CD19, CD34, CD45 and HLA-DR were barely expressed in rPBMSCs. rPBMSCs possessed the potential to differentiate into chondrocytes, adipocytes, and osteoblasts under their respective induction conditions. Cell growth curve and viability experiments were performed under hypoxicconditions: 19% O2, 5% O2, and 1% O2.Specifically,5% O2 accelerated the proliferation and expression of the stemness of PBMSCs. Cycle experiments proved that hypoxia promoted the cell transition from the G1 phase tothe S phase. Molecular experimentsconfirmed that 5% O2 hypoxia significantly elevated the expressions of hypoxia-inducible factor 1α and β-catenin and simultaneously the expressions of cycle-related genes including CyclinE/CDK2 and stemness-related genes including Nanog and SOX2. The appropriate concentration of hypoxia (i.e., 5% O2) enhanced the proliferation and stemness of rPBMSCs and increasedthe multidirectional differentiation potential of stromal cells. The proposed culture method could improve the viability and maintain the phenotype of rPBMSCs in cartilage or bone tissue engineering.